Regeneration of cello-oligomers via selective depolymerization of cellulose fibers derived from printed paper wastes - Lee, Ken Voon; Suh, Cem Pang; Suk, Fun Chin (Elsevier Ltd, 2016)
tCellulose extracted from printed paper wastes were selectively depolymerized under controlledconditions into cello-oligomers of controllable chain lengths via dissolution in an ionic liquid, 1-allyl-3-methylimidazolium chloride (AMIMCl), and in the presence of an acid catalyst, Amberlyst 15DRY. Thedepolymerization process was optimized against reaction temperature, concentration of acid catalyst,and reaction time. Despite rapid initial depolymerization process, the rate of cellulose depolymerizationslowed down gradually upon prolonged reaction time, with 75.0 wt% yield of regenerated cello-oligomers(mean Viscosimetric Degree of Polymerization value of 81) obtained after 40 min. The depolymeriza-tion of cellulose fibers at 80◦C appeared to proceed via a second-order kinetic reaction with respect tothe catalyst concentration of 0.23 mmol H3O+. As such, the cellulose depolymerization process couldafford some degree of control on the degree of polymerization or chain lengths of cello-oligomersformed.